GE_GERICHTE P/414/2020 vom 22. März 2022 - GE Cour de justice (2022)
CLASSEMENT DE LA PROCÉDURE;PARTIE À LA PROCÉDURE;LÉSÉ;CONCURRENCE DÉLOYALE;DÉNIGREMENT;COMPÉTENCE RATIONE LOCI;DIFFAMATION;INJURE;CAS BÉNIN | CPP.319; CPP.310; CPP.382; CPP.115; LCD.3.leta; CP.8; CP.31; CP.173; CP.177; CP.52